Черняхівські "булли" (металеві та шкіряні підвіски-складні в ареалі культури Черняхів—Синтана-де-Муреш) - Гопкало, О.В. (Археологія і давня історія України, 2021)
У складі прикрас культури Черняхів—Синтана-де-Муреш трапляються невеликі металеві або
шкіряні підвіски, складені з двох половинок. Вони
отримали назву умбоноподібних через сферичну випуклість по центру та належать до типу II/11
за запропонованою класифікацією. За низкою ознак їх можна вважати похідними від римської «булли». Судячи за розподілом поховального інвентарю, вони не є маркером поховань осіб певної статі або
віку, але, безумовно, зберегли призначення апотропеїв. Отже, підвіски-складні належали до речей,
пов’язаних із світоглядом, віруваннями варварів доби пізньої античності. Decorations of the Chernyakhiv—Sintana-de-Mures
Culture (ChSM) includes metal and leather pendants
which by some morphological features can be considered
as derivatives of the roman bulla. Bulla is a small
capsule pendant folded from two identical halves. It’s
assumed that bulla originated with the Etruscans in
the VIIth century BC. The bulla was later borrowed
by romans, who originally intended it for boys — the
children of aristocrats from the ninth day of birth to
14—16 years, until receiving the status of a Roman
citizen. Later the golden bulla lost the meaning of a
social marker and became mainly a property feature.
Content of bulla were parts of plants, animal bones,
pieces of textile, sand etc.
Derivatives of the Roman bulla in the ChSM Culture
have been found in next burial complexes (Barcea 139,
Bila 3, Cherneliv-Rus’kyi 96, Dumaniv 8, Sosnova 245),
leather bullas were found once (Legedzine 16). Besides,
two pendants-capsules were found on late Scythians
Lower Dnieper cemetery Mykolaivka (burial 64,
grave 1), which contained ChSM Culture’s graves too.
Following observation deserves the attention. The capacity
of one pendant from Pannonia is similar by decor
to clay knots, which were spread in many cultures, including
ChSM Culture. They are interpreted as magic,
used for fortune-telling and similar to nasturtium seeds.
Contents of Chernyakhiv Culture’s «bullas» are unknown,
but combination with another pendants-amulets
certainly confirms the magical character of such
pendants.
Finally, metal bullae, cylindrical and flat cylindrical
pendants-capsules continued their existence in the
early Middle Ages and as metal folding icons and leather
incenses survived in orthodox church to this day.